Monstress. Volume nine, The possessed - Liu, Marjorie M.; Liu, Marjorie M.; Takeda, Sana (Image Comics, Inc., 2024)
"Maika, Kippa, and Ren return to their own world to discover a full year has passed in their absence--and Zinn is back in the clutches of Maika's father, the megalomaniacal Lord Doctor. From the relative safety of the pirate-controlled Spice Islands, Maika and her friends must regroup, recover, and find a way stop the Lord Doctor's murderous rampage before he destroys the Known World"--